2018
DOI: 10.3390/molecules23010198
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Autism Spectrum Disorder and Melatonin during Fetal Development

Abstract: The aim of this review is to clarify the interrelationship between melatonin and autism spectrum disorder (ASD) during fetal development. ASD refers to a diverse range of neurodevelopmental disorders characterized by social deficits, impaired communication, and stereotyped or repetitive behaviors. Melatonin, which is secreted by the pineal gland, has well-established neuroprotective and circadian entraining effects. During pregnancy, the hormone crosses the placenta into the fetal circulation and transmits pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 60 publications
(83 reference statements)
2
25
0
Order By: Relevance
“…Comorbid conditions may predispose to sleep disturbance, including anxiety, fear, ADHD, sensory attributes, cognitive challenges, repetitive review of activities or anticipation of activity. Children may also have biological and genetic reasons for rapid or slow metabolism of melatonin and dysregulation of the circadian clock . Treatment should be individualised.…”
Section: Sleep Problems and Their Treatment In Specific Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbid conditions may predispose to sleep disturbance, including anxiety, fear, ADHD, sensory attributes, cognitive challenges, repetitive review of activities or anticipation of activity. Children may also have biological and genetic reasons for rapid or slow metabolism of melatonin and dysregulation of the circadian clock . Treatment should be individualised.…”
Section: Sleep Problems and Their Treatment In Specific Disordersmentioning
confidence: 99%
“…Children may also have biological and genetic reasons for rapid or slow metabolism of melatonin and dysregulation of the circadian clock. 17,18 Treatment should be individualised. A recent paper evaluating sensory profiles and sleep disturbance found that hypersensitivity to touch explained 24% of the variance in sleep disturbance in the ASD group, as opposed to other domains such as visual and auditory.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…16,25 Melatonin plays a role of circadian rhythm messenger between mother and fetus, which should be involved in the form of normal fetal sleep patterns and circadian rhythms. 18,19 We speculated that the melatonin regulated the circadian rhythms and brought about the associations between maternal sleep and childhood sleep. There has been evidence to support the association of maternal melatonin with children's sleep by longitudinal observation.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Melatonin, a circadian rhythm messenger linking mother and fetus, has essential functions not only in fetal maturation but also in children's sleep patterns. [18][19][20][21][22][23][24] Because it has been confirmed that sleep disturbance during pregnancy could interfere with the rhythm and amplitude of melatonin secretion, 16,25 we strongly hypothesized that maternal sleep was associated with their offspring's sleep. Two animal studies provided evidence for our hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin deficiency might cause abnormal synaptogenesis. Melatonin secretion is often impaired in ASD [19].…”
Section: Melatoninmentioning
confidence: 99%